Administration of Purified Exosome Product in a Rat Sciatic Serve Reverse Autograft Model. Issue 2 (21st June 2021) - Ikumi, Akira; Gingery, Anne; Toyoshima, Yoichi; Zhao, Chunfeng; Moran, Steven L.; Livia, Christopher; Rolland, Tyler; Peterson, Timothy; Sabbah, Michael S.; Boroumand, Soulmaz; Saffari, Tiam M.; Behfar, Atta; et al.
Abstract : Background: The nerve autograft remains the gold standard when reconstructing peripheral nerve defects. However, although autograft repair can result in useful functional recovery, poor outcomes are common, and better treatments are needed. The purpose of this study was to evaluate the effect of purified exosome product on functional motor recovery and nerve-related gene expression in a rat sciatic nerve reverse autograft model. Methods: Ninety-six Sprague-Dawley rats were divided into three experimental groups. In each group, a unilateral 10-mm sciatic nerve defect was created. The excised nerve was reversed and used to reconstruct the defect. Group I animals received the reversed autograft alone, group II animals received the reversed autograft with fibrin glue, and group III animals received the reversed autograft with purified exosome product suspended in the fibrin glue. The animals were killed at 3 and 7 days and 12 and 16 weeks after surgery. Evaluation included compound muscle action potentials, isometric tetanic force, tibialis anterior muscle wet weight, nerve regeneration–related gene expression, and nerve histomorphometry. Results: At 16 weeks, isometric tetanic force was significantly better in group III ( p = 0.03). The average axon diameter of the peroneal nerve was significantly larger in group III at both 12 and 16 weeks ( p = 0.015 at 12 weeks; p < 0.01 at 16 weeks). GAP43 and S100b gene expression was significantly up-regulated by purified exosome product. Conclusions: Local administration of purified exosome product demonstrated improved nerve regeneration profiles in the reverse sciatic nerve autograft rat model. Thus, purified exosome product may have beneficial effects on nerve regeneration, gene profiles, and motor outcomes.